Preparation, characterization and study of biological activity and laser effect on the new Cu(II) complexes containing mixed benziloxime and furfuraldehydeazine ligands (Baghdad Science Journal, 2025)
Abstract: New copper(II) complexes with mixed ligand benziloxime (BOxH) and furfural-dehydeazine (FA) using classical (with and without solvent) and microwave heating methods have been prepared. The resulting complexes have been characterized using physico-chemical techniques. The study suggested that the ligands formed neutral complexes had general formulas [Cu(FA)(BOXH)(Ac)2] and [Cu(FA)(BOX)(OH)] in neutral (or acidic) and basic medium, respectively. Accordingly, hexa-coordinated mono-nuclear complexes have been investigated by this study and having distorted octahedral geometry. The effect of laser have been studied on solid ligands and solid complexes, no effect have been observed on most compounds through the results of melting point and conductivity, this means that most of the compounds were not affected by this kind of radiation. and stable. Whereas some few complexes have been slightly affected due to breaking of hydrogen bonding. The biological activity of copper salt, ligands and all the complexes have been evaluated by agar plate diffusion techniques against two human pathogenic bacterial strains: Staphylococcus aureus and Enterococcus. Copper acetate was found to have antibacterial activity. The ligand FA also has antibacterial activity against Staphylococcus aureus and Enterococcus, whereas the other ligand BOxH does not have antibacterial activity against Enterococcus. Most of the complexes were found to have antibacterial activity against Staphylococcus aureus and Enterococcus. The activity of the complexes (2,4 and 5) have been evaluated on trace of Impetigo from skin of males and females, the complexes [Cu(BOxH)(FA)(Ac)2] (2) and [Cu(BOx)(FA)(OH)] (4,5); showed significant activity against this pathogen.